Evaluation of Anti-CCP Positive in Patients with Systemic Lupus Erythematosus Referred to Loghman Hakim Hospital between 2007-2017; A Descriptive Study - Emam, Mohammad Mehdi; Shahrbaf, MohamadAmin; Hatam, Maryam; Asaadi, Sina; OmidBeigi, Mahmoud (Student Research in Translational Medicine, 2020)
Background: It has been found that some patients with Systemic lupus erythematosus (SLE) may have anti-cyclic citrullinated peptide antibodies (anti-CCP), although the clinical significance of such finding is not well established. SLE patients may have joint complaints that are very similar to those observed in rheumatoid arthritis (RA). In early stages of disease, this form of arthritis can be difficult to differentiate from RA, so it is not rare that some SLE patients are initially misdiagnosed to have this disease. This study aims to investigate the prevalence of anti-CCP in SLE patients in Loghman Hakim hospital, Tehran, Iran. Method and Materials: One hundred fourteen SLE patients were studied for anti-CCP. Demographic features and prevalence serum positive Anti-CCP were measured in studied patient. Results: In this study we evaluate 11 men and 103 women. The mean age of patients was 40.26±14.54 y/o. Anti-CCP was positive in 20 of 114 SLE patients. In Anti-CCP positive group also there was 3 men and 17 women with mean age of 45.7±13. Conclusion: We found that 17.5 % of Iranian patients with SLE have positive anti-CCP. Only a careful and prolonged follow-up will reveal the real clinical value of these markers in each patient individually. Key Words: Anti-CCP, Rheumatoid arthritis, Systemic lupus erythematosus